Effect of double doping of CUO films with cadmium and cobalt eras on the structural and electrical properties (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this study, CuO thin films were deposited from the preparation of a gelatinous solution of aqueous copper acetate at a concentration of 0.6 M dissolved in 2-methoxyethanol, and mono ethanolamine was added to neutralize the pH of the solution to reach (Ph =7)) onglass bases and double-grafted with cadmium and cobalt in equal proportions